Tutti Fruity (Fresh Fruit Enterprise) / Puteri Nur Aqilah Nor Azizi - Puteri Nur Aqilah, Nor Azizi (2020)
Fresh Fruit is a business which in incorporated on 1st January 2020. Fresh Fruit offers products and service for customer, providing the variety of fresh fruit, buah potong and rojak buah that gives high satisfaction of consumer. The business is located at No 83 Jalan Bandar Seri Iskandar, 31000 Seri Iskandar Perak. Our target market is focused on people that stayed in Seri Iskandar, students and workers in UITM Seri Iskandar that love to eat fruits. As we know that fruit is on of healthy food. Fresh Fruit market potential is to emphasize the quality of fruit and price of our products and service. Fresh Fruit is a partnership business which register under Registration of Business Act in 1956. Into the fruits consists of 5 managers whose are General manager, Administrative Manager, Marketing Manager, Operation manager and Finance Manager. This five partners will be take role responsibilities together instead different duties and portfolio of partners. The business capital is amounted to RM 60 000.00 where contribution of each member is RM 12 000.00.